The Role of the People's Republic of China in International Fragmentation and Production Networks: An Empirical Investigation - Hyun-Hoon Lee; Donghyun Park; Jing Wang (Asian Development Bank (ADB), 2011)
Despite the central role of the People's Republic of China (PRC) in global parts and components trade, most previous studies on the PRC's parts and components trade have been limited to a particular trade partner or some specific industries. The central objective of this paper is to provide a more complete description of the PRC's parts and components trade. To do so, we systematically separate total trade flows into parts and components and final goods, and give a description of the pattern of parts and components trade for the period 1992–2009. We then estimate a gravity model to examine the determinants of the PRC's trade in parts and components. We find that the share of parts and components trade in the PRC's total trade has grown rapidly.
hdl:11540/2008
Keywords: F14; F21; F23; 330; People's Republic of China; PRC; parts and components trade; fragmentation; production network